Enhancement of global competitiveness for Hong Kong/China manufacturing industries through i-agile virtual enterprising. (1st January 2003) - Yam, Richard C.M.; Lo, William; Sun, H.Y.; Tang, P.Y.
A benchmarking study reveals that the current hard development (i.e. hard automation and advanced manufacturing technologies) in Hong Kong is far behind its competitors. Hong Kong should upgrade its middleman role via soft technology advancement in the short and intermediate term. Hong Kong should migrate from mainly Original Equipment Manufacturing (OEM) to Original Design Manufacturing (ODM) and finally to the development of its Own Brand Manufacturing (OBM). A new type of manufacturing paradigm should be established in which Hong Kong will be in charge of the information and soft-technology functions to support manufacturing in China. An internet-based competitiveness model, consisting of an i-marketing intelligent system, an i-global supply chain system, and an i-concurrent engineering system, is required to initiate, support and drive enterprise restructuring. This i-competitiveness model will also facilitate timely new product design and logistics support to HK/China manufacturing operations.